2013
DOI: 10.1007/s00394-013-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in body composition in a sample of Czech women aged 18–89 years: a cross-sectional study

Abstract: BackgroundThe Czech Republic lacks body composition data for women. Therefore, the purpose of the study was to analyze body composition [body fat mass (BFM), fat-free mass (FFM), body fat percentage (%BFM) and visceral adipose tissue (VAT)] and to evaluate the changes that occur with aging in women aged 18–89 years. We also analyzed anthropometric characteristics of study participants and developed age-specific percentile curves for body composition parameters.MethodsA cross-sectional, non‐randomized study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 28 publications
5
51
0
1
Order By: Relevance
“…Similar to those of other authors [4, 30, 33, 34], our present findings also confirmed the decrease in ASM, ASMI, HS, and GS, and the increase in the prevalence rates of low muscle mass, low muscle strength, and low physical performance with age. We observed that ASM was significantly lower among the women aged ≥75 years than among those in the preceding age group (12.76 ± 0.22 kg vs. 14.13 ± 0.15 kg, p  < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to those of other authors [4, 30, 33, 34], our present findings also confirmed the decrease in ASM, ASMI, HS, and GS, and the increase in the prevalence rates of low muscle mass, low muscle strength, and low physical performance with age. We observed that ASM was significantly lower among the women aged ≥75 years than among those in the preceding age group (12.76 ± 0.22 kg vs. 14.13 ± 0.15 kg, p  < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, even though ASM decreased dramatically, body weight just decreased slightly with aging, partly due to the increase in FM (unreported data). The decrease in ASM and increase in FM accompanying aging may lead to the development of sarcopenia and contribute to obesity in the elderly [33]. We also found that muscle strength (HS) and physical performance (GS) decreased more greatly with age than did muscle mass ( p  < 0.001), which was similar to the findings of previous cross-sectional or longitudinal investigations [30, 3538].…”
Section: Discussionsupporting
confidence: 89%
“…Although the results of this study differ from those of some previous studies (Ferreira, da Silva Coqueiro, Barbosa, Pinheiro, & Fernandes, 2013), they are consistent with those of recent studies and suggest that the BMI alone is not an adequate index for all target populations because of age-related body fat redistribution, especially that in older adults (Bhurosy & Jeewon, 2013;S.-H. Chang, Beason, Hunleth, & Colditz, 2012;Gába & Přidalová, 2014). Therefore, it can be assumed that the BMI is not the most appropriate index for assessing visceral fat or predicting the effects of PA, especially in aging adults.…”
Section: Discussionsupporting
confidence: 73%
“…The majority of studies have found that the obesity and low muscle mass may coexist in aging adults (Gába & Přidalová, 2014;Kalyani, Corriere, & Ferrucci, 2014;N. Miljkovic, Lim, Miljkovic, & Frontera, 2015;Sakuma & Yamaguchi, 2013), and obesity and sarcopenia in the aging adults may potentiate each other, maximizing physical disability, morbidity, and mortality (Batsis, Mackenzie, Barre, Lopez-Jimenez, & Bartels, 2014;Benton, Whyte, & Dyal, 2011;Bouchonville & Villareal, 2013;Fragala, Kenny, & Kuchel, 2015;Mathus-Vliegen, 2012;Sakuma & Yamaguchi, 2013).…”
mentioning
confidence: 98%
“…We appreciate that Dr. Umut Safer and his colleagues considered our study [1] interesting and recommended it to readers of the European Journal of Nutrition. With regards to the letter from Safer et al about our recent publication, our responses to the letter are as follows.…”
Section: Dear Editormentioning
confidence: 93%